Utilizing tissue‐engineered cartilage or BMNC‐PLGA composites to fill empty spaces during autologous osteochondral mosaicplasty in porcine knees. (21st February 2014) - Zuo, Qiang; Cui, Weiding; Liu, Feng; Wang, Qing; Chen, Zhefeng; Fan, Weimin
Abstract: The potential empty spaces between cylindrical plugs remaining after autologous osteochondral mosaicplasty rely on fibrous repair, which may constrain the quality and integrity of the repair. Thus, the empty spaces should be repaired, and how to fill the empty spaces is still a problem. In the present study, a standardized full‐thickness defect (diameter, 6 mm) was created in the weight‐bearing area of each medial femoral condyle in both knees of 18 miniature pigs. The 36 knees were randomly assigned to four groups with nine in each group. The defects were initially repaired by autologous osteochondral mosaicplasty. Simultaneously, any empty spaces between the multiple plugs were filled with cell‐free poly(lactide‐co‐glycolide) (PLGA) scaffolds (the scaffold group), tissue‐engineered cartilage (the TE group) or bone marrow mononuclear cell (BMNC)–PLGA composites (the composite group). The empty spaces were left untreated as control (the control group). Six months after surgery, the repair results were assessed via macroscopic observation, histological evaluation, magnetic resonance imaging, biomechanical assessment and glycosaminoglycan content. The results demonstrated that mosaicplasty combined with the treatment of the empty spaces could improve cartilage regeneration. The filling of empty spaces by tissue‐engineered cartilage produced the best result in all the four groups. Meanwhile, utilizing BMNC–PLGA composites achieved a similar repair result. Considering the cost‐effective, time‐saving and convenient performance, the BMNC‐PLGA composite could be an alternative option to fill the empty spaces combined with mosaicplasty. Copyright © 2014 John Wiley & Sons, Ltd.